Enhancement growth, water use efficiency and economic benefit for maize by drip irrigation in Northwest China - Mengjie Liu; Fei Liang; Quansheng Li; Guodong Wang; Yuxin Tian; Hongtao Jia (Scientific Reports, 2023)
Abstract The application of drip irrigation has been paid more and more attention, but there was lack of systematic comparative analysis between drip irrigation and conventional border irrigation method for maize, currently. A 7-year field study from 2015 to 2021 evaluated the effects of drip irrigation (DI, 540 mm) or conventional border irrigation method (BI, 720 mm) on maize growth, water use efficiency (WUE) as well as profitability. The results showed the plant height, leaf area index, yield, WUE and economic benefit of maize with DI had significantly higher than BI. The dry matter translocation, the dry matter transfer efficiency and contribution of dry matter translocation to grain with DI showed significant increase of 27.44%, 13.97% and 7.85% compared to BI, respectively. In comparison to conventional border irrigation, the yield of drip irrigation increased by 14.39%, as well as WUE and irrigation water use efficiency (IWUE) increased by 53.77% and 57.89%. The net return and economic benefit of drip irrigation was 1998.87 and 756.58 USD$ hm−1 higher than that of BI. Drip irrigation increased net return and benefit/cost ratio by 60.90% and 22.88% compared with BI. These results demonstrate that the drip irrigation can effectively improve the growth, yield, WUE and economic benefit of maize in northwest China. Therefore, drip irrigation can be used for maize cultivation to increase crop yield and WUE in northwest China, which has cut down on irrigation water about 180 mm.